«The women’s epidemic»: La mortalidad materna por fiebre puerperal en España en los siglos XIX y XX - Ruiz Berdún, Dolores (Avisos de Viena, 2024)
Puerperal infection has long been one of the most dreaded consequences of childbirth, with a high likelihood of a fatal outcome. Even today, it's estimated that 10% of all maternal deaths globally result from puerperal infection. The infection, often caused by bacteria such as Streptococcus pyogenes, presents with symptoms including fever, chills, abdominal pain, uterine subinvolution, diarrhea, vomiting, foul-smelling lochia, altered mental state, and even shock. If untreated, it can progress rapidly, leading to septicemia and death. Notable historical figures like Mary Wollstonecraft and Ignaz Philipp Semmelweis fell victim to this perilous condition, which prompted investigations into its causes. Early observations by figures like Alexander Gordon in the 18th century suggested a contagious nature, leading to recommendations for hygiene practices among birth attendants. Despite ancient recognition, understanding and combating puerperal fever remained elusive until modern medical advancements.